Pengaruh Tingkat Pendidikan, Pengalaman Kerja, Independensi, dan Gaya Kepemimpinan terhadap Efektivitas SPI BUMD Kota Denpasar - Widya, I Gede Yoga Trisna; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2019)
This study aims to obtain empirical evidence of the influence of the level of education, work experience, independence, and leadership style on the effectiveness of the Denpasar City BUMD Internal Control System. The method of data collection in this study is a survey method. The population is 32 Internal Control Units in 3 (three) BUMD in Denpasar City. The sampling method uses a saturated sample technique, so that the sample used was 32 Internal Control Units. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate the level of education, work experience, independence, and leadership style partially have a positive effect on the effectiveness of the Denpasar City BUMD Internal Control System. Keywords : Level of Education, Work Experience, Independence, Leadership Style, Effectiveness of the Internal Control System